Utilization of orange peel waste for sustainable amino acid production by Corynebacterium glutamicum - SARIYAR AKBULUT, BERNA (My University, 2024)
Oranges are the most processed fruit in the world–it is therefore apparent that the industrial production of orange juice generates large quantities of orange peel as a by-product. Unfortunately, the management of the orange peel waste leads to economic and environmental problems. Meanwhile, the use of sustainable raw materials for the production of bulk chemicals, such as amino acids, is becoming increasingly attractive. To address both issues, this study focused on the use of orange peel waste as a raw material for media preparation for the production of amino acids by engineered Corynebacterium glutamicum. C. glutamicum grew on pure orange peel hydrolysate (OPH) and growth was enhanced by the addition of a nitrogen source and a pH buffer. Inhibitory effects by the combination of high concentrations of OPH, (NH4)2SO4, and MOPS buffer in the wild-type strain (WT), were overcome in the tyrosine-producing engineered C. glutamicum strain AROM3. Genetic modifications that we identified to allow for improved growth rates under these conditions included the deletions of the vanillin dehydrogenase gene vdh, the ʟ-lactate dehydrogenase gene ldhA and the 19 genes comprising cluster cg2663-cg2686. A growth inhibiting compound present in high concentrations in the OPH is 5-(hydroxymethyl)furfural (HMF). We identified vdh as being primarily responsible for the oxidation of HMF to its acid 5-hydroxymethyl-2-furancarboxylic acid (HMFCA), as the formation of HMFCA was reduced by 97% upon deletion of vdh in C. glutamicum WT. In addition, we showed that growth limitations could be overcome by adjusting the media preparation, using a combination of cheap ammonia water and KOH for pH neutralization after acidic hydrolysis. Overall, we developed a sustainable medium based on orange peel waste for the cultivation of C. glutamicum and demonstrated the successful production of the exemplary amino acids ʟ-arginine, ʟ-lysine, ʟ-serine, ʟ-valine and ʟ-tyrosine.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Patoloji; Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Mühendislik ve Teknoloji; Medicine; Surgery Medicine Sciences; Pathology; Biomedical Engineering; Life Sciences; Biotechnology; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Mühendislik; Biyoloji ve Biyokimya; Mikrobiyoloji; PATOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); ENGINEERING; BIOLOGY & BIOCHEMISTRY; MICROBIOLOGY; PATHOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Histoloji; Biyomedikal mühendisliği; Bioengineering; Physical Sciences; Histology; agriculture sidestream; Corynebacterium glutamicum; food waste upcycling; orange peel; second generation feed stock; sustainable amino acid production